STRATEGI KOMUNIKASI HUMAS POLDA RIAU DALAM MENGINFORMASIKAN BAHAYA HOAX DI KOTA PEKANBARU - Ahmad, Hafizal; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Today's information is mostly received through social media because through social media anyone can convey information does not have to be a team of journalists, thus every event that occurs in seconds through social media can be seen and known by the public. Various kinds of information that enter the public through social media cannot be ascertained the truth, sometimes there are many fake news or hoaxes that are considered true by the community so that ordinary people who do not know the truth immediately spread the hoax news, even though since 2008 the ITE law has been enacted. Although laws related to the danger of hoaxes have existed since 2008, hoax news still appears among the people in Pekanbaru. Therefore the Riau Regional Police Public Relations as law enforcement and law must have a communication strategy in informing the danger of hoaxes to the people of Pekanbaru. This study used a descriptive qualitative research method. Subjects in the study were determined based on purposive sampling technique which amounted to four people consisting of members of the Riau Police Public Relations and Pekanbaru city community. The technique of collecting data through interviews, observation and documentation. The data analysis technique uses the interactive data model of Miles and Huberman by checking the validity of the data using triangulation techniques. The results showed that the Riau Police Public Relations had the credibility and attractiveness of the source as an expert communicator by disseminating information and having knowledge about the environment and trustworthiness, namely the Riau Police Public Relations informing the danger of hoaxes by applying the law-abiding nature. The message used consists of verbal messages, including clarity, innocence and accuracy. While nonverbal messages by giving examples of law-abiding perilau and using symbols. The media used is divided into two: internal communication media and external communication media.